Fabrication of a composite modified glassy carbon electrode: a highly selective, sensitive and rapid electrochemical sensor for silver ion detection in river water samples. Issue 28 (7th July 2016) - Azhari, Syaza; Sathishkumar, Palanivel; Ahamad, Rahmalan; Ahmad, Farediah; Mohd Yusoff, Abdull Rahim
Abstract : A glassy carbon electrode was modified with multi-walled carbon nanotubes, 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim]PF6 ), N, N ′-bis(2-hydroxyacetophenone)ethylenediamine and Nafion to form a MWCNT-BZE-[bmim]PF6 -Nafion-GCE. Abstract : In this study, a glassy carbon electrode (GCE) was modified with multi-walled carbon nanotubes (MWCNTs), 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim]PF6 ), N, N ′-bis(2-hydroxyacetophenone)ethylenediamine (BZE) and Nafion to form a MWCNT-BZE-[bmim]PF6 -Nafion-GCE. The electrochemical behaviour of the modified electrode with respect to silver (Ag(i )) ion detection was studied by cyclic voltammetry (CV) and differential pulse anodic stripping voltammetry (DPASV). Furthermore, the experimental parameters including the pH value of Britton–Robinson Buffer (BRB), Nafion, MWCNTs, BZE and ([bmim]PF6 ) concentrations and the deposition potential and time were optimized. The detection limit of the modified electrode for the Ag(i ) ion was found to be 70 ng L −1 (6.49 × 10 −10 mol L −1 ). Repetitive measurements revealed good reproducibility with a relative standard deviation (RSD) value of 0.4%. The system performance of the modified electrode was highly satisfactory and the recoveries for river water samples were found to be 96–121%. This study proved that the MWCNT-BZE-[bmim]PF6 -Nafion-GCE is a highly selective and sensitive modified electrode for the detection of the Ag(i ) ion in river water samples with good recovery value.